Dynamic behavior of a polyurethane foam solidified ballasted track in a heavy haul railway tunnel. Issue 3 (February 2019) - Cai, Xiaopei; Zhong, Yanglong; Hao, Xiaocheng; Zhang, Yanrong; Cui, Rixin
Dynamic behavior of a new type of track using the polyurethane foam solidified ballast in heavy haul railway tunnels is comprehensively investigated in this study. First, a dynamic model of the vehicle–track–tunnel interaction system was developed based on the multi-body system dynamics theory and finite element method. Then, the dynamic effects of the polyurethane foam solidified ballast track on the train and the surrounding infrastructures were calculated and compared to those of the traditional ballasted track. Moreover, the effects of the elastic modulus and the solidified area size of polyurethane foam solidified ballast on the dynamic behavior were analyzed. Results show that, compared to the traditional ballast bed, polyurethane foam solidified ballast decreases the track stiffness and the vibration acceleration of the tunnel, while does not affect the vehicle safety (derailment coefficient and the rate of wheel load reduction). A larger elastic modulus of polyurethane foam solidified ballast has little effects on the wheel–rail interaction and the vibration acceleration of the tunnel, while a smaller modulus results in amplification of the displacements of rails and sleepers. Considering the vehicle–track interaction and tunnel vibration, the optimal elastic modulus of polyurethane foam solidified ballast is suggested to be 60–80 MPa. In addition, smaller solidified area of polyurethane foam solidified ballast presents lower effects on the vibration reduction and rate of wheel load reduction, while larger area leads to a higher derailment coefficient and cost. Therefore, an optimal solidified area size of polyurethane foam solidified ballast with the top width of 0.85 m is recommended.